Principles of microeconomics - Case, Karl E. (Prentice Hall, 1996)
Extensive coverage of policy issues and real world applicationsincluding "Issues and Applications" boxes, international isintegrated throughout the text including "Global Perspective"boxes, new end-of-chapter problem sets, 10 end-of-part case studies with critical thinking questions (each supported by a video) and aunified approach to theory.